IMPLEMENTASI KODE ETIK DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU (Studi pada Madrasah Ibtidaiyah Darus Salam Al Islami Kabupaten Tebo) - Sungkowo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to analyze the implementation of the teacher code of ethics in improving the pedagogical competence of Islamic education teachers at Madrasah Ibtidaiyah Darus Salam Al Islami Tebo. The research methodology is descriptive qualitative case study, with data collection techniques through observation, interviews, and documentation. The subjects of this study are Islamic education teachers. The results of this study prove that the implementation of the teacher code of ethics can improve the pedagogical competence of Islamic education teachers, which has three indicators, namely moral, emotional, and spiritual maturity, self-development, and student-centered orientation. The conclusion of this study is that the implementation of the teacher code of ethics is carried out in several stages, namely the head of the madrasah conducts periodic and scheduled socialization of the teacher code of ethics at the beginning of each semester, followed by supervision and evaluation of the implementation of the teacher code of ethics. The obstacles to implementing the teacher code of ethics are that there are still teachers who do not fully understand all the details of the regulations containing the teacher code of ethics, and there are still teachers whose moral, emotional, and spiritual maturity needs to be improved. Efforts to implement the teacher code of ethics in improving the pedagogical competence of teachers include requiring Islamic education teachers to attend socialization sessions on various professional codes of ethics for teachers and seminars related to codes of ethics and the teaching profession.